Effect of Ndonga (Paste of Mixed Spices) on Some Metabolic Parameters in Rats Fed With a High-Calorie Diet. (14th June 2022) - Angie, Mary-Ann Mbong; Azantsa, Boris Gabin; Ntentie, Francoise Raissa; Nwang, Felix; Oben, Julius; Orang, Remy
Abstract: Objectives: The beneficial role of spices on health has long been proven. In Cameroon, spices are mostly been consumed as a mixture added in meal preparations not for their health benefits but for their capacity to enhance the taste or the flavour of the meals. Therefore, associating the health advantages with the culinary properties will make it possible to better valorize these spices largely consumed by Cameroonian populations. Thus the present work aimed at evaluating the effect of Ndonga (a paste of mixed spices) on some biological parameters in rats fed with a high-calorie diet. Methods: The paste was purchased from a local manufacturer and vendor in Kumbe-Bakundu, South-West Region, Cameroon. Part of the spice mixture was macerated in distilled water (1:6w/v) for 24 h and the filtrate was used to assess for bioactive compounds. The other part was used to supplement at 5 and 10% a High-fat high sucrose diet (HFHSD) used to feed rats (treated groups). The experimentation included a rat group fed with a normal diet (ND) and a positive control group fed with no supplemented HFHSD. Body weight was registered for all rats throughout the experimental period that lasted 28 days. Fasting blood and organs collected from rats were used for biochemical assays. Results: Bioactive molecules such as polyphenols and flavonoids were present in the prepared aqueous extract. Total antioxidant capacity and DPPH scavenging capacity were both found to be more important in the acidified water extract. In vivo results revealed that weight gain was least important (+3, 05%) in the group supplemented with 10% Ndonga compared to all the other groups (P < 0.05) as well as a lower triglyceride level (69, 2 ± 9, 31 mg/dL) (p< 0.05). Apart from the normal group where food consumption was lowest, food intake was similar in all groups. HDL-cholesterol level was higher in the group supplemented with 5% Ndonga (P < 0.05). Liver and kidney parameters were found to be ameliorated in supplemented groups. Conclusions: Supplementation of meals with Ndonga can ameliorate lipid metabolic disorders and thus prevent atherogenic risk. Funding Sources: The present work did not receive any funding.